The influence of beta-adrenoceptor blockers with and without intrinsic sympathomimetic activity on heart rate, arrhythmias and ST-T segments, using ambulatory electrocardiography. - Northcote, R J (1988)
1. Ambulatory electrocardiography was used to compare the effects of propranolol and pindolol on symptoms, heart rate, arrhythmias and ST segments. Seventeen males (mean age 54 years) with a diagnosis of chronic stable angina pectoris (New York Heart Association Class II-III) were studied. Patients were treated on a double-blind cross-over basis with propranolol 80 mg three times daily or pindolol 5 mg three times daily for 14 days each. During the last 48 h of each treatment period ambulatory electrocardiography was performed. 2. Propranolol resulted in a significantly lower mean hourly, mean 24 h and minimum heart rate. Likewise propranolol caused a lower mean daytime and nocturnal heart rate. There was no significant difference in the frequency of angina between the treatments. The number of episodes of ST segment depression was not significantly different between the two drugs, although there was a trend in favour of propranolol. 3. Both the mean 24 h ST level and the maximum ST segment depression were lower during treatment with pindolol. Propranolol was associated with a total of 117 nocturnal pauses or episodes of asystole ranging in length from 1.5 to 2.8 s. During treatment with pindolol only one such period occurred. The number of premature ventricular contractions occurring during treatment with pindolol (1316 beats) was less than on propranolol (2010) and the mean hourly frequency of premature ventricular contractions was significantly lower during pindolol administration. 4. Pindolol is not significantly different from propranolol in the control of symptomatic and asymptomatic myocardial ischaemia and is associated with fewer premature ventricular contractions. However, there is no advantage in using pindolol in chronic stable angina.